"You have ruined this entire experiment…shall we stop talking now?" Orientations to the experimental setting as an interactional resource. (December 2016) - MacLeod, Nicci; Grant, Tim
Abstract: One limitation widely noted in sociolinguistics is the tension presented by the 'observer׳s paradox' (Labov, 1972), i.e. the notion that everyday language is susceptible to contamination by observation (Stubbs, 1983: 224). The observer׳s paradox has been perceived to present significant challenges to traditional sociolinguistic researchers seeking to explore the processes at work during ordinary interaction. More recently, scholars have begun to argue that in fact the presence of a recording device, rather than being a mere constraint on spoken interaction, is in itself an interactional resource explicitly oriented to by participants (Speer and Hutchby 2003; Gordon 2012). Drawing on a collection of transcripts collected in experimental conditions as part of a wider project exploring the relationship between language and identity, this paper seeks to explore how these orientations manifest themselves in the context of Instant Messaging (IM) conversations. We show different orientations to the experimental setting, and different understandings of the role of the researcher – represented in this case by the IM chat archive – as both a topic of discussion and as a participant themselves. Highlights: Data from a set of Instant Messaging (IM) experiments are analysed. Participants regularly display an orientation to being recorded. Participants exploit the process in order to fulfil a range of activities. Knowledge of being recorded cannot satisfactorily be viewed as a mere constraint.